PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA SISWA MELALUI MODEL DISCOVERY LEARNING BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Nur Ilahi, Anisa; Fadhilaturrahmi; Yanti Yandri Kusuma; Rusdial Marta; Rizal, Muhammad Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' understanding of mathematical concepts in class IV UPT SD Negeri 007 Bangkinag Kota. The background of this research is the low understanding of mathematical concepts of students in class IV. This researcher is a classroom action research, which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study were 1 teacher and 14 students, while the object was to use discovery learning to increase students' understanding of mathematics concepts. This assessment instrument consists of a teacher activity observation sheet, student activity observation sheet, documentation sheet, learning test sheet during learning by using the discory learning model. While the data analysis techniques used are qualitative and quantitative description analysis. Based on the results of tests conducted in cycle I meeting I showed that there were 4 students (28.57%) out of 14 students who were included in the very poor category (<60), and in cycle I meeting II showed that there were 7 students (50%) out of 14 students who were included in the poor category (<60), while in cycle II meeting I showed that there were 8 students (72.28) out of 14 students who were included in the good enough category and in cycle II meeting II showed 12 students (81.07) out of 14 students who were included in the good category (80-89%). By using the discovery learning model, it can improve the understanding of mathematical concepts of fourth grade students of UPT SD Negeri 007 Bangkinag Kota.